PEMBIASAAN IBADAH DAN DAMPAKNYA TERHADAP KARAKTER DISIPLIN SISWA: STUDI KASUS DI SMP NEGERI 1 BANYUMAS - Ratna Tri Wiharti; Muh Hanif (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
Creating a disciplined school character is one of the key objectives of modern education, particularly at the junior high school level. This research is based on the importance of implementing worship habituation programs as a managerial strategy to shape student discipline at SMP Negeri 1 Banyumas. The main focus of this study is to describe and analyze the worship habituation program and its impact on students’ disciplinary character, as part of the educational management framework. The research methodology employed in this case is qualitative in nature. Data were collected through observation, interviews, and documentation. Data analysis was conducted in stages, including data reduction, data presentation, and finally drawing conclusions. The results of the study show that a systematically implemented and well-integrated worship habituation program within school management can influence students' discipline character in aspects such as attendance, punctuality, obedience to rules, and personal responsibility. Therefore, this finding contributes to educational stakeholders in designing management strategies that emphasize the role of religious values in building student discipline.